The Bowhead vs. the Gray Whale in Chukotkan Aboriginal Whaling - Krupnik, Igor I. (ARCTIC, 1987)
Active whaling for large baleen whales - mostly for bowhead (Balaena mysticetus) and gray whales (Eschrichtius robustus) - has been practiced by aborigines on the Chukotka Peninsula since at least the early centuries of the Christian era. The history of native whaling off Chukotka may be divided into four periods according to the hunting methods used and the primary species pursued: ancient or aboriginal (from earliest times up to the second half of the 19th century); traditional (second half of the 19th century to the 1930s); transitional (late 1930s to early 1960s); and modern (from the early 1960s). The data on bowhead/gray whale bone distribution in the ruins of aboriginal coastal sites, available catch data from native settlements from the late 19th century and local oral tradition prove to be valuable sources for identifying specific areas of aboriginal whaling off Chukotka. Until the 1930s, bowhead whales generally predominated in the native catch; gray whales were hunted periodically or locally along restricted parts of the coast. Some 8-10 bowheads and 3-5 gray whales were killed on the average in a "good year" by Chukotka natives during the early 20th century. Around the mid-20th century, however, bowheads were completely replaced by gray whales. On the basis of this experience, the author believes that the substitution of gray whales for bowheads, proposed recently by conservationists for modern Alaska Eskimos, would be unsuccessful.Key words: bowhead, gray whale, aboriginal whaling, Chukotka, Asiatic Eskimos, Chukchis Depuis au moins les premiers siècles de l'ère chrétienne, les aborigènes de la péninsule Chukotka ont fait une chasse active aux grandes baleines à fanons, en particulier la baleine boréale (Balaena mysticetus) et la baleine grise de Californie (Eschrichtius robustus). L'histoire de cette chasse autochtone à la baleine au large de la péninsule Chukotka peut être divisée en quatre périodes selon les méthodes de chasse utilisées et les espèces primaires poursuivies: la période ancienne ...